Characteristics and local structure of hafnia‐silicate‐zirconate ceramic nanomixtures. (8th June 2020) - Pop, L.; Rada, S.; An, P.; Zhang, J.; Rada, M.; Suciu, R. C.; Culea, E.
Abstract : Zirconate systems having the composition 3HfO2 ·15SiO2 · x Y2 O3 ·(82 − x )ZrO2, where x = 2, 7 and 12 mol% Y2 O3, were synthesized by a sol‐gel method. Their characteristics and local structure are described. Abstract : Zirconate systems having the composition 3HfO2 ·15SiO2 · x Y2 O3 ·(82 − x )ZrO2, where x = 2, 7 and 12 mol% Y2 O3, were synthesized by a sol‐gel method. The analysis of X‐ray diffraction data showed the presence of the t‐ZrO2, m‐ZrO2, m‐HfO2, Y2 SiO5 and Y2 Si2 O7 crystalline phases in a ceramic nanomixture. Spectroscopic data show that the increase of the Y2 O3 content of samples determines the increase of the t‐ZrO2, m‐HfO2 and silicate crystalline phases. Gap energy values decrease almost linearly with increasing Y2 O3 content of samples. A detailed study of XANES data does not show a significant difference with increasing Y2 O3 content of the samples suggesting an appreciable stability of the hafnium ions +4 oxidation state and their microvicinity. EXAFS results show that the local structure around the Hf cation is similar to that from the monoclinic crystalline HfO2 where the Hf–O coordination number tends to 7. The bond lengths of Hf–O shells show small deviations from ∼2.12 Å and the Hf–metal paths become more structured by increasing the Y2 O3 content of the samples.